Language Barriers and Academic Interaction of Indonesian Postgraduate Students in Abroad - Ferawaty Syam; Herman Resyadi; Nugrah Juniar Umar; Hardianti; Widya Rizky Pratiwi; Syahrir Nawir Nur (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2026)
This study explores how Indonesian postgraduate students in Queensland University cope with language barriers in academic contexts through the use of personal strategies and institutional support. The research employed a qualitative design using semi-structured interviews. Two postgraduate students were selected through purposive sampling based on their length of study and experiences as international students. Data were analyzed thematically to identify recurring patterns and themes. The results show that students adopted various self-directed strategies, such as active participation in academic and social forums, practicing spoken English with peers, and engaging in extensive reading. Both participants also emphasized the importance of institutional support, including English conversation clubs, academic workshops, and Artificial Intelligence-related training programs, which significantly enhanced their academic engagement. Preparation for advanced academic tasks varied, one participant focusing on structured training and competitions, while the other emphasized content mastery and relied on institutional services to refine language skills. The study concludes that overcoming language barriers requires a combination of individual initiative and systematic institutional support, highlighting the need for integrated approaches to assist international students in academic settings.